Frequency of Maternal Intrapartum Complications of Macrosomic Fetus - Maria Iqbal, Aqsa Latif, Naeem Akhtar Khokhar, Amna Begum, Ayesha Samad Dogar, Kausar Masoom, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Macrosomia is a clinical problem that can lead to birth injury, intervention, postpartum haemorrhage and other adverse outcomes. Incidence of macrosomia has increased in the last 10-20 years. Objective: To determine the frequency of maternal intra partum complication of macrosomic fetus. Material and Methods: The study was conducted at Afridi Medical Complex and Teaching Hospital Tehkal Peshawar. Duration of this study was one year from May 2022 to May 2023. In this study a total of 97 (nearly 100 patients) keeping 20% prevalence of instrumental vaginal deliveries, 95% confidence level and 8% precision value. More over it was a descriptive (cross sectional) study in which non probability consecutive sampling technique was used. Results: In this study most of the patients 70% were in age range 30-45 years, 85% patients had POG 37-40 weeks, 80% patients were multigravidas, 30% had post date pregnancy, 40% patients were obese and 30% patients were diabetic in which 5% had chronic diabetics and 25% patients had gestational diabetics. Thirty five maternal intrapartum complications were found among 100 patients, in which 14% patients had shoulder dystocia, 26% patients had caesarean section, 6% patients had instrumental delivery, 26% patients had genital tract trauma and 29% patients had post partum haemorrrhage. Conclusion: Our study concludes that the frequency of maternal intrapartum complications of macrosomic fetus is high. With increasing in number of diabetes and obesity, the incidence of macrosomia and hance its consequences are increasing. With timely anticipation and managing the complication maternal as well as fetal morbidity can be reduced. Keywords: Frequency; Maternal intrapartum; Complications; Nacrosomic fetus